New Insights on Biofilm Antimicrobial Strategies, 2nd Volume - Azevedo, Andreia S. (2022)
In biofilms, microorganisms are able to communicate together and assemble by themselves, creating a consortium with different properties from the original free-floating microorganisms [...]